Biochar application to low fertility soils: A review of current status, and future prospects - El-Naggar, Ali; Lee, Sang Soo; Rinklebe, Jörg; Farooq, Muhammad; Song, Hocheol; Sarmah, Ajit K.; Zimmerman, Andrew R.; Ahmad, Mahtab; Shaheen, Sabry M.; Ok, Yong Sik (Geoderma, 2019)
Rapid industrial development and human activities have caused a degradation of soil quality and fertility. There is increasing interest in rehabilitating low fertility soils to improve crop yield and sustainability. Biochar, a carbonaceous material intentionally produced from biomass, is widely used as an amendment to improve soil fertility by retaining nutrients and, potentially, enhancing nutrient bioavailability. But, biochar is not a simple carbon material with uniform properties, so appropriate biochar selection must consider soil type and target crop. In this respect, many recent studies have evaluated several modification methods to maximize the effectiveness of biochar such as optimizing the pyrolysis process, mixing with other soil amendments, composting with other additives, activating by physicochemical processes, and coating with other organic materials. However, the economic feasibility of biochar application cannot be neglected. Strategies for reducing biochar losses and its application costs, and increasing its use efficiency need to be developed. This review synthesized current understanding and introduces holistic and practical approaches for biochar application to low fertility soils, with consideration of economic aspects. •Biochar has potential to be the best management practice for low fertility soils.•Biochar coating with organic materials can result in enhanced crop nutrient supply.•Biochar may accelerate the composting process and improve the end-product quality.•The influence of biochar varies strongly according to the types of feedstock/soil.